The demand for public buses in sub-Saharan African cities: Case studies from Maputo and Nairobi. (July 2019) - Tembe, Atanasio; Nakamura, Fumihiko; Tanaka, Shinji; Ariyoshi, Ryo; Miura, Shino
Abstract: Despite the limited transportation options, public buses have been proved unpopular in many Sub-Saharan African cities. While the declining use of local buses in the developed world is often associated with increasing number of transport alternatives, relatively little is known about African cities. A substantial number of studies are focused on how to replace buses with the rapid transportation modes and less diagnosis is applied to the factors affecting the use of buses. Using household information survey, this paper attempts to investigate the factors affecting the demand for buses in Maputo and Nairobi by employing logistic regression approach. Results show both similarities and variations among the factors affecting the likelihood of using buses. For example, the likelihood of using buses decreases with vehicle ownership and employment status in the two cities. In addition, gender (female) has no effect on the likelihood of choosing buses over paratransit in both cities. Second, while age decreases the likelihood of choosing buses and residence location increases that in Maputo, the opposite is observed in the case of Nairobi City. The main implication of these findings is that there is a need to share the roles of public transportation between buses and paratransit. Highlights: Declining use of public buses in Sub-Saharan African cities despite the growing demand for transport Similarities and variations among the factors affecting the likelihood of using buses The likelihood of using buses decreases with vehicle ownership and employment status in Maputo and Nairobi Gender has no effect on the likelihood of choosing buses over paratransit in both cities Policymakers should consider sharing the roles of public transportation between buses and paratransit